CERITA RAKYAT PULAU MAYA KABUPATEN KAYONG UTARA (KAJIAN STRUKTUR, FUNGSI, KONTEKS, DAN NILAI BUDAYA) - Sumiati, Tuti; Effendy, Chairil; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis presents a study that focuses on the study of oral literature, namely folklore. The rapid development of Science and Technology has led to a reduction in speakers and listeners of folklore, for that careful study of folklore texts needs to be done. The focus of the problem in this study is the structure, function, context and cultural value of the story and its implementation plan in learning folklore in schools. The method used is descriptive analysis. This research uses structural approach and sociology of literature. The data source in this study is in the form of folklore told by speakers. The steps of data collection are done by recording, transcribing, editing, translating, identifying and classifying. The data is then interpreted and analyzed by providing interpretations of meaning according to the problem under study. The results of the analysis of this study are: (1) the structure of the story, there is a forward plot, there is a human character, and there is a setting in the form of place, time setting and social setting; (2) the function of the story, found five functions, namely: as a means of entertainment; as a means of education and inculcation of moral values; as a cultural validator; as a means to pass down traditional ways of life, customs and habits; and as a tool so that the norms of society will always be obeyed by their collective members; (3) the narrative context consists of three contexts namely situation context, cultural context, and social context; (4) cultural values consist of human relations with God, human relations with oneself, human relations with the natural surroundings, and human relationships with each other; and (5) the results of this study can be implemented in Bahasa Indoneisa learning in schools because there are positive values that can be learned by students, namely in KD 3.7 identifying the values and content contained in folklore both oral and written, and KD 4.7 retell the contents of folklore heard and read. Keywords: Context, Cultural Values, Folklore, Function, Structure